Evolving Identity in the Face of Imperialism and Colonialism: The Emergence and Development of Political Islam (Critical Journal of Social Sciences, 2026)
This paper applies the Constructivist approach to analyse the role of identity in Islamism, or political Islam, in order to complement and, in some cases, problematise the theories that have sought to explain that ideology. It focuses on mainstream Islamism in the Sunni Arab world and references the work of prominent scholars and theorists to illustrate their thought.The core of the paper is divided into five sections: The first considers the genesis of Islamism as a response to the ontological threat posed by the West. The second explains how Islamists relate to an idealised past which they also see as a model for the future. The third section argues that the project to create an Islamic state reflects a desire to produce a non-secular modernity. The fourth dwells on the reinvention of tradition by Islamist thinkers to legitimise their interpretation of Islam and their wide-reaching programme of social transformation. The fifth and last section discusses how Islamists “Other” members of the community who are reluctant to embrace their project.